Les relations internationales de l'après-guerre froide: une mutation globale - Seminatore, Irnerio (Études internationales, 1996)
The author analyzes the post-Cold War international arena thoroughly, be delineating one by one Us different systemic, geopolitical, hegemonic, and strategic metamorphoses. The emergence of a fragmented transnational subsystem — the social component of the international System — has made this era fertile ground for third-wave conflicts, i.e. cultural conflicts or shocks between civilizations. The lack of any recognized leadership and the collective exercise of the system's governability may lead one to observe that armed violence is being waged by means other than those of major inter-state wars. In such a context, one may deduce that emphasis on the concept of collective security is working to the detriment of defence-minded thinking and to the benefit of strategies for active and very early conflict prevention. The entire realm of strategy is thus open to a wide-ranging, Worldwide arena. The main consequences have been an end to the old custodial arrangements of geopolitics, thereby transforming NATO in Europe, and a renewed activism in Asia, where the trend is towards creation of a specific security subsystem. These transformations of the international System have brought about metamorphoses in the notions of enemy, boundary, conflict, and power. Such changes also highlight the « rationality deficit » now affecting the System and the proliferation of the notion of « meaning », which is everywhere lacking in consistency. The shifting of the security dilemma to the subnational, internal level has accordingly resulted from the breakup of nations and the decolonization of empires. The author concludes that it may prove useful, even valuable, to try and identify the normative elements of the post-Cold War international System and to outline, however imperfectly, the new distribution of international power. The reader will also find afresh look at the doctrinal debate about international System theory and about the epistemology of the discipline that deals with it.